Complete genome sequence of a natural compounds producer, Streptomyces violaceus S21 - Fu, Jiafang (Genom Data, 2017)
The complete genome sequence of Streptomyces violaceus strain S21, a valuable natural compounds producer isolated from the forest soil, is firstly presented here. The genome comprised 7.91M bp, with a G + C content of 72.65%. A range of genes involved in pathways of secondary product biosynthesis were predicted. The genome sequence is available at DDBJ/EMBL/Genbank under the accession number CP020570. This genome is annotated with 6856 predicted genes identifying the natural product biosynthetic gene clusters in S. violaceus.